Case report: Neonatal autoimmune lymphoproliferative syndrome with a novel pathogenic homozygous FAS variant effectively treated with sirolimus - Elgharbawy, Fawzia M.; Karim, Mohammed Yousuf; Soliman, Dina Sameh; Hassan, Amel Siddik; Sudarsanan, Anoop; Gad, Ashraf (Frontiers in Pediatrics, 2023)
Background: The autoimmune lymphoproliferative syndrome (ALPS) is a rare disease characterized by defective FAS signaling, which results in chronic, non-malignant lymphoproliferation and autoimmunity accompanied by increased numbers of double-negative (DN)T cells (T-cell receptor αβ+ CD4–CD8–) and an increased risk of developing malignancies later in life. Case Presentation: We herein report a case of newborn boy with a novel germline homozygous variant identified in the FAS gene, exon 9, c.775del, which was considered pathogenic. The consequence of this sequence change was the creation of a premature translational stop signal (p. lle259*), associated with a severe clinical phenotype of ALPS-FAS. The elder brother of the proband is also affected by ALPS and has been found to have the same FAS homozygous variant associated with a severe clinical phenotype of ALPS-FAS, whereas the unaffected parents are heterozygous carriers of this variant. This new variant has not previously been described in population databases (gnomAD and ExAC) or in patients with FAS-related conditions. Treatment with Sirolimus effectively improved the patient clinical manifestations with obvious reduction in the "double negative" T cells percentage. Conclusion: We described a new ALPS-FAS clinical phenotype-associated germline FAS homozygous pathogenic variant, Exon 9, c.775del, that produces a premature translational stop signal (p. lle259*). Sirolimus significantly reduced the percentage of "double-negative" T cells, and substantially relieved the patient's clinical symptoms.